The safety and efficacy of additional chest tube placement in patients with prolonged air leaks after pulmonary resection: a propensity score-matched analysis - Hua, Qingwang; Liu, Suyue; Shen, Lu; Yang, Zhenhua; Shen, Haibo (Frontiers in Medicine, 2024)
Background This study evaluates the symptomatic management of prolonged pleural air leaks following pulmonary resection, assesses the efficacy and safety of chest tube placement, and introduces experiences with high-positioned chest tube insertion. Methods We retrospectively reviewed 84 patients with prolonged pleural air leaks after lung surgery at Ningbo No.2 Hospital from January 2022 to December 2023. These patients were divided into a conservative treatment group (Group A, n = 64) and a chest tube placement group (Group B, n = 20). The propensity score matching method was applied to balance confounders between the two groups, resulting in 12 matched pairs. The study compared the time to chest tube removal, average hospital stays time, postoperative drainage volume, and facial visual analog pain score between the two groups. Results The average hospital stays and chest tube removal time of patients in group B were significantly lower than those of patients in group A (8.00 ± 1.12 vs. 9.75 ± 1.60 days, P = 0.003, 6.92 ± 1.08 vs. 8.58 ± 1.67 days, P = 0.005, respectively). However, the mean facial visual analog pain score in group B was higher than that in group A (1.58 ± 0.58 vs. 1.00 ± 0.01, P = 0.020). There were no significant differences between the two groups in terms of postoperative drainage volume. Conclusions For patients with prolonged air leaks, additional chest tube placement postoperatively significantly reduces both hospitals stay duration and chest tube indwelling time compared to conservative treatment. This method may be a potential treatment measure for prolonged air leak in selected patients.